Nurse management of glycemia in cardiac intensive care. (25th November 2020) - Cappannelli, S; Cosmi, D; Rey, L; Murrone, A
Abstract: Introduction: Scientific studies have shown that hypoglycaemia is an important risk factor for adverse events in cardiac intensive care. Nursing management of blood glucose, via protocol, is an important tool to avoid cases of hypoglycaemia. Objective: We evaluate the efficacy and safety of a glycemia control protocol based on nursing management in diabetic patients in Intensive Care Unit. Material and methods: We conducted a retrospective analysis on 500 patients hospitalized for acute coronary syndrome or heart failure, with an average age of 75±12 years, clinically stable. The protocol used provides, on medical indication, the suspension of home therapy (both oral hypoglycemic agents and insulin) and the introduction of insulin therapy according to the scheme 0.2/0.5 IU/kg/day. The dosage lower than 0.2 IU/kg/day is used for patients in home therapy with oral hypoglycemic agents and basal blood sugar <150 mg/dl and the dose greater than 0.5 IU/kg/day for patients already on home insulin therapy and basal blood sugar> at 200 mg/dl. The intermediate dosage. 3–0.4 IU/kg/day is instead used in patients with glycaemia between 150 and 200 mg/dl regardless of home therapy. On the basis of the dosage schedule, the daily insulin requirement is obtained which is then administered at 50% as a slow analogue at 10 pm and at 50% as a rapid analogue, further divided into three doses with each main meal. Once the initial therapy has been set, the nurse acts autonomously according to a correction algorithm (based on the calculation of the correction factor (FC) according to the formula FC = 3000/body weight in kg or FC = 1700/total daily dose of insulin > FC = reduction in blood glucose in mg/dl determined by 1 IU of insulin) which provides for the modification of insulin therapy based on the patient's weight and the blood glucose values measured with sticks at 8, 12, 18 and 22. If during hospitalization and/or discharge, inadequately controlled glycemic values persist, the patient is sent to diabetes advice and the current home therapy is resumed upon discharge or according to diabetes advice. Results: We observed an excellent pre and post prandial glucose control with extremely reduced incidence of hypoglycaemia which occurred in only 3 cases, one of which with severe hypoglycaemia (glucose detected <40 mg/dl, resolved with the administration of glucose 33 20ml% followed by infusion of 10% glucose solution and glycemic stick after 15') for administration error and two with moderate hypoglycaemia (glucose detected between 40–70 mg/dl resolved with the reduction of 2 IU of rapid analogue and repeated stick post prandial). Conclusions: A nursing management protocol for blood glucose values in patients with diabetes mellitus hospitalized for acute coronary syndrome or heart failure is safe and allows good control of blood glucose values. Funding Acknowledgement: Type of funding source: None